\[\boxed{\mathbf{572\ (572).\ }Еуроки\ - \ ДЗ\ без\ мороки}\]
\[1)\ \frac{1}{\sqrt{3} + 1} \cdot \left( \sqrt{3} - 1 \right) =\]
\[= \frac{\left( \sqrt{3} - 1 \right)}{\left( \sqrt{3} - 1 \right)\left( \sqrt{3} + 1 \right)} = \frac{\sqrt{3} - 1}{3 - 1} =\]
\[= \frac{\sqrt{3} - 1}{2}\]
\[2)\ \frac{1}{\sqrt{5} + \sqrt{3}} \cdot \left( \sqrt{5} - \sqrt{3} \right) =\]
\[= \frac{\sqrt{5} - \sqrt{3}}{\left( \sqrt{5} + \sqrt{3} \right)\left( \sqrt{5} - \sqrt{3} \right)} =\]
\[= \frac{\sqrt{5} - \sqrt{3}}{5 - 3} = \frac{\sqrt{5} - \sqrt{3}}{2}\]
\[3)\frac{1}{\sqrt{7} + \sqrt{5}} \cdot \left( \sqrt{7} - \sqrt{5} \right) =\]
\[= \frac{\sqrt{7} - \sqrt{5}}{\left( \sqrt{7} + \sqrt{5} \right)\left( \sqrt{7} - \sqrt{5} \right)} =\]
\[= \frac{\sqrt{7} - \sqrt{5}}{7 - 5} = \frac{\sqrt{7} - \sqrt{5}}{2}\]
\[4)\frac{1}{\sqrt{91} + \sqrt{89}} \cdot \left( \sqrt{91} - \sqrt{89} \right) =\]
\[= \frac{\sqrt{91} - \sqrt{89}}{\left( \sqrt{91} + \sqrt{89} \right)\left( \sqrt{91} - \sqrt{89} \right)} =\]
\[= \frac{\sqrt{91} - \sqrt{89}}{2}\text{\ \ }\]
\[5)\ У\ всех\ дробей\ знаменатель\ \]
\[будет\ общий\ (2),\ а\ в\ числителе\ \]
\[получим:\]
\[Получаем\ дробь:\ \frac{\sqrt{91} - 1}{2}\text{.\ \ }\]